SETTLEMENT OF CONSUMER DISPUTES THROUGH THE BANDUNG CITY CONSUMER DISPUTES RESOLUTION AGENCY (BPSK) - Hartini, Rahayu; Rahma, Tannasya Putri (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
The Consumer Dispute Settlement Body (BPSK), in accordance with Law No. 8 of 1999 regulating Consumer Protection (UUPK) is regulated by the government, has a role to handle and resolve problems arising between consumers and business actors. The purpose of establishing BPSK is to reduce the complexity and time required in court proceedings, which are often long and difficult, by providing an out-of-court dispute resolution shortcut, focusing on the principles of speed, simplicity, and affordable costs. This study focuses on the Consumer Dispute Settlement Body in Bandung City, using a normative legal approach. In brief, the purpose of BPSK is to avoid resolving consumer disputes through the public courts. The general court is long and costly, but BPSK makes a fast and even cheap procedural law. The author analyzes legal literature related to consumer protection and consumer dispute resolution, and then compiles and classifies it in a detailed, systematic, and directed manner. The data collected is then analyzed descriptively to provide a comprehensive picture of the problem of consumer dispute resolution at BPSK Bandung City.